Apologetic Ideas in the Works of St. Athanasius the Great - Penkov, Dimo (Forum Theologicum Sardicense, 2025)
Dimo Penkov, Apologetic Views in the Early Works of St. Athana-sius the Great. The aim of this paper is to examine the apologetic strategies and the methodology of the early works of St. Athanasius. This essay focuses on the two most important early works of St. Athanasius “Against the Heathen” and “On the Incarnation of the Word”.